Evaluation of route-to-route extrapolation factors based on assessment of repeated dose toxicity studies compiled in the database RepDose®. (2nd November 2016) - Schröder, K.; Escher, S.E.; Hoffmann-Dörr, S.; Kühne, R.; Simetska, N.; Mangelsdorf, I.
Highlights: R2R extrapolation factors (oral-to-dermal and oral-to-inhalation) are derived based on no/lowest effect levels (NOELs/LOELs) in the Fraunhofer RepDose ® database. R2R extrapolation oral-to-inhalation: the analysis is based on a big dataset consisting of 246 study pairs on 110 chemicals. Extrapolation factors and associated uncertainties are evaluated. An EF of 3 for the extrapolation oral-to-inhalation is proposed. It covers also the uncertainty that unexpected local effects may occur in an inhalation study. Abstract: The majority of repeated dose toxicity studies are available for the oral route. For risk assessment, however, data are needed from the relevant exposure route, i.e. inhalation or dermal. Instead of conducting additional animal studies, route-to-route (R2R) extrapolation may be performed. To explore uncertainties associated with this approach, we derived extrapolation factors (EF) based on no/lowest effect levels (NOELs/LOELs) in the Fraunhofer RepDose ® database. For R2R extrapolation oral-to-inhalation 246 study pairs on 110 chemicals were analyzed. Systemic effects triggered the LOELs in the underlying inhalation studies in 49.2%, local effects in 21.9% and both local and systemic effects in 30.9% of the data pairs. For systemic effects in inhalation studies an EF of 2.2 (95% confidence interval: 1.2–3.1) was derived, for local effects, the EF was 4.4 (95% confidence interval: 2.0–8.6), and the EF without distinguishing local or systemic effects (any EF) was 3.2 (95%, confidence interval: 1.7–5.0). Calculation with LOELs instead of NOELs, exposure duration and intrinsic properties of the chemical (toxicity or physicochemical properties) did not influence the EF significantly. For R2R extrapolation oral-to-dermal 46 study pairs on 28 chemicals were analyzed. An overall EF of 0.4 (95%, confidence interval: 0.2–0.9) was obtained. Here, we found a significant difference of EFs for low and high toxic chemicals. Overall, we conclude that reliable systemic NOELs/LOELs can be obtained for inhalation studies via R2R extrapolation from oral studies. Based on the data for any EF we propose to use an EF of 3, which covers also the uncertainty that unexpected local effects may occur in an inhalation study. For the dermal route, our dataset was too small to allow general conclusions, but the results so far do suggest that the current ECHA guidance is conservative when assuming that dermal absorption is as high as oral absorption.